Zaagtoonaa Nibi (We Love the Water): Anishinaabe community-led research on water governance and protection - Latulippe, Nicole; McGregor, Deborah (The International Indigenous Policy Journal, 2022)
This paper presents Indigenous community-led, collaborative, and community-engaged water governance research with a First Nations community in the Georgian Bay and Lake Huron region in northeastern Ontario, Canada. The methodology draws on Indigenous approaches to understanding and developing knowledge and is designed to build community capacity in research and in water protection and governance. This approach recognizes existing community strengths, including traditional knowledge, experiences, perspectives, and associated cultural perspectives and values, laws, responsibilities and lived experience in relation to water. Results identify and contextualize community-held responsibilities and legal principles pertaining to water that support culturally relevant water governance and strategic planning. By synthesizing and extending previous water protection initiatives, this research meaningfully supports the community’s position and leadership on water security and governance. This, in turn, strengthens Indigenous water governance and sustainable water governance broadly as Indigenous understandings and approaches to water are holistic and concern relationships with and responsibilities to all of Creation.